ANALISIS RASIO PROFITABILITAS PADA PT. PETRONA MINING CONTRACTORS DI SAMARINDA - -, Denny Saputra (EKONOMIA, 2014)
Profitabilty is the ratio which aims to determine the companyâ€™s ability to generate profits for a certain period and also given an idea of the effectiviness of management in their operation. The problem of this papare is fomulated : Profitabilty is at. Petrona mining contractors has increased from year 2011-2012 ? By hypothesis Profitability at. Petrona mining contractors from 2011 to 2012 has increased. The purpose of this study was determine the level of profitability at. Petrona mining contractors in samarinda from 2011-2012.Â Â Â Â Â Â Â Â Â Â Â Basic theory used is financial management by using tools of analysis and hypthesis testing are : Net Profit Margin, Retrun On Assets.Based on these discussion, it is generally known that the ratio of profitability at PT. Petrona Mining Contractors tend to fluctuate from year 2011-2012, so in this case the authors hypothesis is rejected, given the propsed hypothesis is the author of â€œ Profitability in PT. Petrona Mining Contractors from 2011 to 2012 has increasedâ€.